Design of Synthetic Strategies towards Sulfur Containing Scaffolds - Kotha, Sambasivarao; Khedkar, Priti (Synthesis, 2024)
The utilization of sulfur heterocycles in organic synthesis has attracted significant attention due to their wide-ranging applications. This review showcases the syntheses of diverse sulfur heterocycles embedded with amino acid derivatives, polycycles, spirocycles, cyclophanes, and other complex scaffolds. The reported methods extend beyond compound synthesis and highlight the use of different sulfur reagents for constructing sulfur heterocycles. This Review also discusses the utility of a variety of sulfur-containing starting materials for the generation of complex target molecules.1 Introduction2 Potassium Thioacetate3 Thiazolidine-2,4-dione4 Rhodanines5 Sodium Sulfide6 Thiotetronic Acid7 Thiadiazoles8 Thiophene9 Rongalite10 Sulfur Dioxide11 Divinyl Sulfone12 Sulfur Heterocycles Based on Boronic Acids13 Miscellaneous14 Summary
Keywords: sulfur heterocycles; potassium thioacetate; thiazolidine-2,4-dione; rhodanines; thiotetronic acid; thiadiazole; thiophene; rongalite